Saúde mental para profissionais da saúde do estado de São Paulo no contexto da pandemia COVID-19 - Aldrighi, Andrea; Gonçalves Moura, Denise; Ribeiro, Eliana; Shimma, Emi; de Fátima Chibante Fortes, Lúcia; Dias S. Magalhães, Luciana; Maria Piovesan, Rosane; Alencar Coutinho, Roxane; Santos Silva, Zeni; Elias, Rosangela; et al. (BEPA. Boletim Epidemiológico Paulista, 2020)
.